2002
DOI: 10.1530/eje.0.1460629
|View full text |Cite
|
Sign up to set email alerts
|

TNF-alpha gene polymorphism and plasma TNF-alpha levels are related to lumbar spine bone area in healthy female Caucasian adolescents

Abstract: Objective: The cytokine tumor necrosis factor alpha (TNF-a) is an important regulator of bone metabolism. Polymorphisms in the promoter region of the TNF-a gene at positions 2 308 and 2 863 have been identified. We investigated whether these polymorphisms and circulating TNF-a levels were related to bone mineral density and bone area in adolescent girls. Design: Bone mineral density (BMD), bone area (BA), anthropometric characteristics and biochemical analyses were measured in adolescent girls and compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…Patients with the G/G genotype showed increased BMD in the lumbar spine in response to treatment while those with the G/A genotype did not. The genotype distribution of our patients was similar to the European distribution, with more than 70% having the G/G genotype, although different from Asia, where the AA genotype predominates [15,19,20] .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Patients with the G/G genotype showed increased BMD in the lumbar spine in response to treatment while those with the G/A genotype did not. The genotype distribution of our patients was similar to the European distribution, with more than 70% having the G/G genotype, although different from Asia, where the AA genotype predominates [15,19,20] .…”
Section: Discussionsupporting
confidence: 71%
“…However, no significant association was found between the TNF ␣ -308 G/A polymorphism and the incidence of coronary disease [15] or osteoporosis (BMD) either in Europeans or Asians [19,20] . Nor does the polymorphism influence the peak bone mass although another polymorphism located in the promoter region of the gene, -863 CA [19] , does. Only Fontova et al [23] , in a study on 104 postmenopausal women with osteoporosis and 51 without, found a higher bone mass in a group of patients with nonsevere osteoporosis and the G allele.…”
Section: Discussionmentioning
confidence: 95%
“…The fibrinogen ␤-455G/A promoter polymorphism was analyzed as described by Thomas et al 28 The CRP-1059G/C polymorphism was analyzed as described by Zee et al 29 The ICAM-1 K/E469 polymorphism was analyzed as described by Nishimura et al 30 The IL-6 -174C/T promoter polymorphism was analyzed as described by Fishman et al 24 The TNF-␣-238G/A promoter polymorphism was analyzed as described by Wennberg et al 31 The genotype was determined in all individuals and monozygosity was confirmed. In each PCR run, samples with known genotypes were included.…”
Section: Methodsmentioning
confidence: 99%
“…It is overexpressed in adipose tissue, which is both a source of and a target for TNF-α [10,46]. TNF-α has been shown to stimulate bone resorption in vitro and in vivo being also implicated in diseases with increased osteoclastic bone resorption [53,54]. In addition, direct evidence of a stimulatory effect by TNF-α on osteoclastogenesis has been found in both human [55] and mouse [56] bone marrow cells.…”
Section: Il-6mentioning
confidence: 99%